HUBUNGAN ANTARA PERSONALITI DENGAN TAHAP PREJUDIS TERHADAP GOLONGAN KURANG UPAYA INTELEKTUAL - Mohd Ariff Shah, Nurul Syafika; Alias, Atini (Jurnal 'Ulwan, 2023)
The stigma against people with intellectual disability (ID) leads to a discrimination problem that will become a thorn in Malaysia. The existence of this stigma is caused by prejudicial attitudes and stereotypical beliefs against certain minority groups. Both factors existed not only due to social environment, social identity, or social-group membership, but they also existed because of internal attributes of the individual. Hence, the purpose of this study is to identify the relationship between personality and prejudices against people with ID among students of Faculty of Social Sciences at University of Melaka. This survey has been conducted towards 159 students of Faculty of Social Sciences. The study was conducted using quantitative methods and survey methods. The instruments used were The Inventory of Big Five Personality (BFI) and Italian Modern and Classical Prejudices Scale (MCPS-IT). The data was analysed through descriptive and inference statistics that includes T-Test and Pearson Correlation via Statistical Packages for Social Sciences (SPSS) version 25.0. The result shows that there is no significant relationship between personality and prejudices based on gender, education level, and age. Moreover, the study also shows that there is no significant relationship between personality and prejudices scale against people with ID among students of Faculty of Social Sciences (r = 0.027, p > 0.05). In conclusion, personality does not affect the level of prejudices against people with ID.